Giant nevus comedonicus of the entire lower left limb protecting from the associated bullous pemphigoid: A hypothetical role of NEK9 mutation?. Issue 8 (17th May 2021) - Herzum, Astrid; Cozzani, Emanuele; Micalizzi, Claudia; Russo, Roberto; Castelli, Riccardo; Parodi, Aurora
Abstract: We present the case of a 92‐year‐old woman, with bullous pemphigoid (BP) and a concomitant nevus comedonicus (NC) presenting as an asymptomatic, linear lesion of the entire lower left limb, formed by multiple comedones. Dermoscopy of the NC and histopathology confirmed the clinical and dermoscopic suspect of giant congenital nevus comedonicus. The two entities presented no overlap. In this article, we speculate that a mutation of the NEK9 gene, associated with NC, probably altering the normal follicular differentiation in NC lesions, may hypothetically also influence the expression of BPAG2 in NC. This might possibly influence a protective role of NC lesions towards BP. Undoubtedly, genetic studies would be needed to confirm or reject the proposed hypothesis.